Revision of the Palaeohispanic epigraphic material from Ensérune (Hérault, France) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The revision of the epigraphic material written in Levantine script conserved in the reserves of the Museum (Ensérune, Hérault, France) authorizes us to reassess the provenance of many objects. We can then assert that some of them are produced in the kilns of Roses (Catalonia), and outline the integration of the site of Ensérune in the logic of a local economy. We were also able to specify the chronology of several graffiti, by fixing them in 3rd c. B.C.
Keywords: Iberian Epigrapy; Material; Datation; Campanian Ceramics; Roses Ceramics